Development of Contextual-Based Teaching Materials Planning Course at UIN Sumatera Utara, Medan - Zunidar, Zunidar (Didaktika Religia, 2022)
Based on the need for teaching materials designed to meet learning needs, this study aims to analyze the feasibility of teaching materials for the Learning Planning course and the effectiveness of teaching materials for the Learning Planning course. The research method used is development research. Experts validated the teaching materials developed, then continued by individual tests, small group tests, and field groups. Testing the effectiveness of the learning model is done by testing the t-test statistics. The research findings are: first, the teaching materials for the Contextual-Based Learning Planning course show the feasibility level for use in learning activities for the Learning Planning course. Second, the learning Planning course's teaching materials are proven effective for use in learning. The results of statistical testing that the calculated price (5.34)> t table (1.99) proved it, so it can be concluded that the teaching materials developed are effective in improving student learning outcomes.